Test coverage analysis of UML state machines - Ricardo D. F. Ferreira (2010)
Software testing is a very important activity of the software development process. To expedite the testing process and improve the quality of the tests, models are increasingly used as a basis to derive test cases automatically - a technique known as model-based testing (MBT). Given a system model and a test suite derived automatically from the model or created by other process, the coverage of the model achieved by the test suite is important to assess the quality and completeness of the test suite early in the software development process. This paper presents a novel tool that shows visually the coverage achieved by a test suite on a UML state machine model. The tool receives as input a UML state machine model represented in XMI and a test suite represented in a XML format, and produces a colored UML state machine model that shows the coverage result. Model test coverage is determined by simulating the execution of the test suite over the model. An example is presented in order to show the features of the tool. © 2010 IEEE.